Clinico-pathological profile of bronchiolitis in Dhaka Medical College Hospital, Bangladesh - Hossain, Rumi Myedull; Shams, Samina; Begum, Ruksana; Rahman, M. Mujibur; Hasan Khan, M. Mahmud; Nag, Bikash C.; Saha, Uttam K. (International Journal of Contemporary Pediatrics, 2025)
Background: Bronchiolitis is a lower respiratory tract infection characterized by obstruction of small airways caused by acute inflammation, edema and necrosis of the epithelial cells. It is mostly present in infants aged three to six months. The most common etiology is the respiratory syncytial virus (RSV) with the highest incidence of RSV infection occurring between December and March. This study was undertaken to assess clinico-pathological profile of children affected by bronchiolitis. Methods: This descriptive cross-sectional observation study was conducted at department of paediatrics, Dhaka medical college and hospital (DMCH), Dhaka, Bangladesh between January to December of 2013. To find out the clinico-epidemiological and radiological profile of bronchiolitis. Children below 24 months of age diagnosed as bronchiolitis were studied. Results: 100 children were evaluated, including 73 boys and 27 girls; Infants below 6 months accounted for the highest proportion (64%). All the bronchiolitis patients had runny nose, cough or cold with respiratory distress. Other symptoms were feeding difficulty (56.0%) and fever (46.0%). On examination lower chest in drawing and rhonchi were found in all cases. Increased translucency (82%) and hyperinflation (77%) was the most prevalent radiological findings. Conclusions: Most children present with typical clinical and radiological feature of bronchiolitis which can help the clinicians to clinically identify this disease more efficiently.